Implementation of Computer Based Information as Learning Medium for Train Passngers at Railway Station’s Kisaran - M. Fahrul Abdi; Arie Rafika Dewi; Dedy Irwan (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
Information and communication technology has developed along with globalization, so that the interaction and delivery of information occurs quickly. Computers really feel the need and importance of developing and improving quality in conveying the education that will be given by passengers, especially for passengers who want to take the train at the Kisaran city station, education is a process to assist passengers in providing information which will later be carried out using the information. good. For that we need a media in educating passengers who want to ride the train at the Kisaran city station, namely by creating a website where there are several guidelines so that passengers can understand the rules during the covid 19 period well. One way to solve the above problems is using the Computer Based Instruction method, which is to provide information guides such as regulations at the Kisaran city station in the form of procedures for buying train tickets, and types of masks, and others who will be informed. The working principle of the computer based instruction (CBI) method is a programmed learning that uses a computer as a tool to communicate information to people who want to take a train from Kisaran city station.